2020
DOI: 10.1101/2020.09.16.300749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Circuit Mechanisms Underlying Thalamic Control of Attention

Abstract: SummaryThe thalamus is a key brain structure engaged in attentional functions, such as selectively amplifying task-relevant signals of one sensory modality while filtering distractors of another. To investigate computational mechanisms of attentional modulation, we developed a biophysically grounded thalamic reticular circuit model, comprising excitatory thalamocortical and inhibitory reticular neurons, which captures characteristic neurophysiological observations from the alert behaving animals. Top-down atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 94 publications
(163 reference statements)
0
5
0
Order By: Relevance
“…Microstate analysis leverages the excellent temporal resolution of EEG [64] and a meta-criterion on global field power [89], favoring the highest signal-to-noise ratio [16]. The proposed computational circuit mechanisms [37] have presented selective attention [15] as cortical excitability alterations by the thalamus [43] acting as a "spotlight, " which is postulated for the error-related brain state changes [44]. Here, the microstate approach for a brain state correlates of the response [73] to error has a crucial a priori assumption that only one spatial topography map entirely defines the relevant global state of the brain at each moment in time and the residuals are considered noise.…”
Section: Introductionmentioning
confidence: 99%
“…Microstate analysis leverages the excellent temporal resolution of EEG [64] and a meta-criterion on global field power [89], favoring the highest signal-to-noise ratio [16]. The proposed computational circuit mechanisms [37] have presented selective attention [15] as cortical excitability alterations by the thalamus [43] acting as a "spotlight, " which is postulated for the error-related brain state changes [44]. Here, the microstate approach for a brain state correlates of the response [73] to error has a crucial a priori assumption that only one spatial topography map entirely defines the relevant global state of the brain at each moment in time and the residuals are considered noise.…”
Section: Introductionmentioning
confidence: 99%
“…This overlooks experimental findings showing convergent inputs from multiple cortical areas to individual thalamic neurons, 97 rich heterogeneity in wiring across cortical layers that project to/from the thalamus, 7 and diversity in the membrane properties across thalamic neurons, 98 which may place additional constraints on computation in CTC loops. Finally, the thalamic reticular nucleus mediates local inhibition in the thalamus and alters its dynamical regime, 99 which we did not consider in our models.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is, to the best of our knowledge, the most detailed model of its kind created so far, it is only a first step. Future studies will further refine the thalamoreticular model to take into account newly observed cellular and synaptic properties (Li et al, 2020; Martinez-Garcia et al, 2020), and explore thalamoreticular contributions to other functions, such as attention and the generation of the alpha rhythm (Ahrens et al, 2015; Chen et al, 2016; Gu et al, 2021; Makinson and Huguenard, 2015; Nestvogel and McCormick, 2021), when considered in the broader context of the thalamocortical loop.…”
Section: Discussionmentioning
confidence: 99%